The influence of the initial microstructure of die-casting steel on heat treatment results - Kakaš, Damir; Šiđanin, Leposava; Bajić, Vladimir (Journal of Production Engineering, 1989)
This paper presents the influence of the initial microstructure of die-casting steel C.4751 on the results of heat treatments. These treatments were conducted using a furnace with a controlled atmosphere, a vacuum furnace, and salt baths. The best results were achieved with specimens treated in salt baths, thanks to the optimal cooling rate conditions. However, the toughness results obtained from the specimens treated in salt baths never matched the standards' recommendations, primarily due to the inappropriate initial microstructure of the steel.